An Overview for the Potentials of Additive Manufacturing: Polymers Recycling Project in Egypt (American Journal of Innovation in Science and Engineering, 2023)
Additive manufacturing is a star-rising technology around the globe. It satisfies key needs in different fields of interest on a global scale. For both ongoing industrial revolutions, it is considered an enabler as well as for achieving certain Sustainable Development Goals. Regarding the manufacturing sector, the technology serves well for different delicate fields like aerospace, automotive and medicine. Polymers are amongst the wide range of materials that are utilized in additive manufacturing. They provide indispensable mechanical properties in different fields as they possess light weight with high strength and toughness. The existence of polymers in the form of waste is massive, especially after the outbreak of COVID-19. The calls for sustainable development are global. Exploitation of polymer wastes as a feedstock material for additive manufacturing can be considered an opportunity to be seized by Egyptian manufacturers. Such that producing new products, reducing wastes and costs. These piles of waste may now be viewed as wealth. Under the umbrella of the current reforms and developments taking place in the country this can be called upon to be a national project. The paper presents an overview for the opportunity of establishing such a national recycling project in Egypt that depends on 3d printing.